0 votes

To find the value of (x+6)(x+6) = 256, you first need to simplify the left hand side of the equation:

(x+6)(x+6) = x^{2} +6x +6x + 36 = x^{2} + 12x + 36

Substituting this to the original equation will give you this x^{2} + 12x + 36 = 256, which can further be simplified by moving all terms to the left. Doing that will give you the quadratic form (ax^{2} + b^{2} + c = 0) of the equation:

x^{2} + 12x - 220 = 0

Remember that the roots can be obtained by using the quadratic formula given by:

x = [(-b)±√b^{2}-(4ac)] / 2a where a, b, c are the coefficients of the equation. That is, *a* = 1, *b* = 12 and *c* = -220

Substituting the values will give you:

x = [-(12)±√(12)^{2}-(4*1*-220)] / 2(1)

x = [-12±√144-(-880)] / 2

x = [-12±√1024] / 2

x = [-12±32] / 2

First root now equals to:

x = [-12+32] / 2

**x = 10**

Second root:

x = [-12-32] / 2

**x = -22**

There you have it. **The values of x are 10 and -22.**

0 votes

(x+6)(x+6)=256

take sqr root of each side

x+6=16

x= 16 - 6

x= 10

x+6= -16

x= -16 -6

x= -22

we find two answers x= 10 and x= -22

`

take sqr root of each side

x+6=16

x= 16 - 6

x= 10

x+6= -16

x= -16 -6

x= -22

we find two answers x= 10 and x= -22

`

0 votes

The Value of x in the equation (x+6)(x+6)=256

(x+6)(x+6)=256

X^{2}+6x+6x+36=256

X^{2}+12X+36=256

(X+6)^{2}=256 {(a+b)^{2}=a^{2}+2ab+b^{2}}

X+6=16 (take sqr root)

X=16-6

X=10

Ans: X=10

0 votes

(X+6)(X+6)=256

(X+6)^2=256

(X+6)= 256^(1/2)

X+6=+16

X=22

And

X+6=-16

X=-10

You can also solve by making the quadratic equation and solve for that equation.

Any square root have a two solution

(X+6)^2=256

(X+6)= 256^(1/2)

X+6=+16

X=22

And

X+6=-16

X=-10

You can also solve by making the quadratic equation and solve for that equation.

Any square root have a two solution

0 votes

let assume t = x+6

(x+6)(x+6) = 256 => t*t = 256

t^{2} = 256^{ }

^{ t = + or - 16}

^{x + 6 = +16 => x = 10 and x + 6 = -16 => x = -22}

x have two values +10 and -22

^{ }

^{ }

^{
}

^{
}

0 votes

Hi!

I have explained the answer in details with step by step procedure as an image file. I think this must help to you to understand clearly.

0 votes

Simple approach to solve this :

(x+6)(x+6)=256

(x+6)^{2 }= 256

(x+6)^{2} = 16^{2}

^{
}

therefore, (x+6) = 16 or (x+6) = -16

Let's solve x+6=16

=> x = 16-6 =10

Now, Lets solve x+6=-16

=>x= -16-6 = -22

therefore x = 10 ,-22 for given equation!!

0 votes

Given that:

(x + 6)(x + 6) = 256

= (x + 6)^{2 }= 256

Taking square root on both the sides,

= (x + 6) = (+-)16

Hence two values for x possible,

**Case 1:**

x + 6 = 16 **==>** x = 16 - 6 = 10 **==>** **x = 10**

**
**

**Case 2:**

x + 6 = -16 **==> **x = -16 - 6 = -22 **==> x = -22**

**
**

Hence, x = **10, -22**

- All categories
- Ads + Affiliate Money 46
- Animals+Birds 89
- Arts+Literature 48
- Beauty+Fashion 93
- Blog+Seo+Internet 254
- Business+Finance 308
- Cars+Vehicles 72
- Computers+Laptops 100
- Entertainment+Films 99
- Food+Drinks+Cooking 196
- Gadgets+Electronics 140
- Gaming+Sports 135
- Health+Fitness 567
- History+Politics+Society 134
- Home+Garden 77
- Fashion+Clothing 40
- Jobs+Education 261
- Love+Relationships 312
- Mathematics+IQ challenge 18
- Mental Health & Psychology 116
- Religion+Spirituality 133
- Science+Technology 264
- Softwares+OS+Programming 129
- Travel+Places 103
- Others+Miscelleneous 699

4,778 questions

20,022 answers

6,708 comments

4,539 users